Avaliação e tratamento da dor patelofemoral: uma análise de aspectos biomecânicos e psicológicos envolvidos nessa desordem musculoesquelética - Vasconcelos, Gabriela Souza de (Universidade Federal de São Carlos, 2022)
Patellofemoral pain (PFP) is one of the most common forms of knee pain and has a negative impact on physical activity level and quality of life of patients. People with PFP have decreased hip and knee muscle strength and power, kinematic changes during functional activities, and impairment of psychological aspects, such as high kinesiophobia. Although hip and knee muscle strengthening has been recognized as the treatment with the best level of evidence, it is not known whether the addition of power exercises to a muscle strengthening program would result in greater benefits than a strengthening program alone. Furthermore, the relationship between kinesiophobia and isometric hip and knee torque with hip and knee kinematics during a jump is unclear. Finally, although the Knee Injury and Osteoarthritis Outcome Score (KOOS) and the Global Rating of Change (GROC) are widely used in people with PFP to evaluate the effects of treatments, the available information does not allow the proper interpretation of the results in adolescents and adults with PFP. Because of this, this research was based on four studies. The first study is the randomized clinical trial protocol, which aimed to verify whether the benefits of a strength and power training program for hip and knee muscles are superior to those observed in a strength training program alone. People with PFP would be randomized into two intervention groups: Strength and Power Training Group (SPTG) and Strength Training Group (STG). Both groups would perform training sessions three times a week for 12 weeks. Primary outcomes were pain intensity (Numeric Pain Scale) and physical function (Anterior Knee Pain Scale), and secondary outcomes were kinesiophobia (Tampa Scale for Kinesiophobia), quality of life (Knee Injury and Osteoarthritis Outcome Score - KOOS, Quality of Life subscale), peak isometric torque and rate of torque development (RTD) of hip and knee muscles, and self-perception of improvement (Global Rating of Change). Statistical analysis would follow the principles of intention-to-treat. The second study presents the partial results of the randomized clinical trial, which aimed to verify if the benefits of a strength and power training program for hip and knee muscles are superior to those observed in a strength training program alone. To this purpose, 37 participants with PFP, of both sexes, were randomly assigned to two groups: SPTG (n=18) and STG (n=19). Primary outcomes (pain intensity and physical function) were measured at baseline, after 6 weeks, post-intervention and at 3-, 6- and 12-month follow-ups. Secondary outcomes (kinesiophobia, quality of life, peak isometric torque) were measured at baseline and post-intervention. Self-perception of improvement was assessed only at post-intervention. The analysis showed that there was no significant difference between two groups for any of the outcomes assessed at any time point. Regarding the Global Rating of Change results, in the SPTG, 38.88% (n=7) of participants reported a successful in treatment (better or much better), while in the STG, 36.84% (n=7) reported a successful in treatment. The third study aimed to evaluate the relationship between kinesiophobia and hip and knee torque with hip and knee kinematics during single-leg drop vertical jump in women with PFP. Thirty women participated in the study and were assessed for kinesiophobia (Tampa Scale for Kinesiophobia), peak isometric hip extensor, hip abductor, and knee extensor torque (isokinetic dynamometer), and peak hip adduction, hip internal rotation, and knee flexion (three-dimensional motion analysis system) during single-leg drop vertical jump. After a Pearson correlation analysis, weak correlations were found between increased kinesiophobia and increased peak hip internal rotation angle (r=0.43; p=0.018), as well as between greater peak knee extensor torque and greater peak knee flexion (r=0.41; p=0.022). There were no other correlations between the variables. The fourth study aimed to describe how change scores on the KOOS correspond to GROC levels in adolescents and adults with PFP. This was done using secondary data analysis from three clinical trials and involved four hundred and twenty-three adolescents and adults with PFP. Participants completed the KOOS (5 subscales) at baseline and 3-month follow-up, and the Global Rating of Change at 3-month follow-up. The Global Rating Change levels were combined into five categories: worse, no change, a bit better, better, and much better. Analysis was performed using the Receiver Operator Curve (ROC curve) and Predictive Modeling and Adjusted Modeling (logistic regression). It was found that participants who reported being "worse" had negative change scores on all 5 KOOS subscales (≤ -3); participants who reported being "no change" had change scores close to 0 (-8 - 4); and participants who reported being "a bit better" showed minimal change on the KOOS (1 - 13). In addition, participants who reported being "better" or "much better" had positive KOOS change scores (6 - 25 and ≥11, respectively).
Evaluation and treatment of patellofemoral pain: an analysis of the biomechanical and psychological aspects involved in this musculoskeletal disorder
Keywords: Joelho; Síndrome da dor patelofemoral; Força muscular; Exercícios terapêuticos; Reabilitação; Qualidade de vida; Knee; Patellofemoral pain syndrome; Muscle strength; Therapeutic exercises; Rehabilitation; Quality of life; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL